Household Transmission Dynamics of Seasonal Human Coronaviruses. (9th November 2022) - Quandelacy, Talia M; Hitchings, Matt D T; Lessler, Justin; Read, Jonathan M; Vukotich, Charles; Azman, Andrew S; Salje, Henrik; Zimmer, Shanta; Gao, Hongjiang; Zheteyeva, Yenlik; Uzicanin, Amra; Cummings, Derek A T
Abstract: Background: Household transmission studies inform how viruses spread among close contacts, but few characterize household transmission of endemic coronaviruses. Methods: We used data collected from 223 households with school-age children participating in weekly disease surveillance over 2 respiratory virus seasons (December 2015 to May 2017), to describe clinical characteristics of endemic human coronaviruses (HCoV-229E, HcoV-HKU1, HcoV-NL63, HcoV-OC43) infections, and community and household transmission probabilities using a chain-binomial model correcting for missing data from untested households. Results: Among 947 participants in 223 households, we observed 121 infections during the study, most commonly subtype HCoV-OC43. Higher proportions of infected children (<19 years) displayed influenza-like illness symptoms than infected adults (relative risk, 3.0; 95% credible interval [CrI], 1.5–6.9). The estimated weekly household transmission probability was 9% (95% CrI, 6–13) and weekly community acquisition probability was 7% (95% CrI, 5–10). We found no evidence for differences in community or household transmission probabilities by age or symptom status. Simulations suggest that our study was underpowered to detect such differences. Conclusions: Our study highlights the need for large household studies to inform household transmission, the challenges in estimating household transmission probabilities from asymptomatic individuals, and implications for controlling endemic CoVs. Abstract : In our respiratory viral surveillance study, we found that 21% of endemic coronavirus infections were acquired from household members. We found no evidence that transmissibility was different for asymptomatic individuals or for children but were likely underpowered to detect such differences.